2010
DOI: 10.1089/end.2009.0541
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Clinical Trials Presented at the World Congress of Endourology: How Is the Quality of Reporting?

Abstract: Although representing a small portion of the overall number of abstracts, there has been a steady increase of presentation of RCTs at the WCE over the assessed 3-year period. Most of the time they are recognized as RCTs in the abstract title. When applying the CONSORT criteria, necessary information to assess their methodologic quality is incomplete in some cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…They reported that RCTs quantitatively increased from 1.09% of the original articles in the 1980s to 2.63% in the 2000s and that the Jadad scale increased from one point in the 1980s to 2.17 points in the 2000s. As for quality assessment in urology, Autorino et al extracted RCTs from abstracts presented at the World Congress of Endourology (WCE) annual meeting during 2004-2006 and assessed them according to the Consolidated Standards for the Reporting of Trials (CONSORT) statement [14]. They reported that RCT was described in the title of the abstracts in most cases, that RCTs accounted for a small portion of the total abstracts, and that only a small number of abstracts satisfied the CONSORT criteria.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that RCTs quantitatively increased from 1.09% of the original articles in the 1980s to 2.63% in the 2000s and that the Jadad scale increased from one point in the 1980s to 2.17 points in the 2000s. As for quality assessment in urology, Autorino et al extracted RCTs from abstracts presented at the World Congress of Endourology (WCE) annual meeting during 2004-2006 and assessed them according to the Consolidated Standards for the Reporting of Trials (CONSORT) statement [14]. They reported that RCT was described in the title of the abstracts in most cases, that RCTs accounted for a small portion of the total abstracts, and that only a small number of abstracts satisfied the CONSORT criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, objective methodological quality assessment of published studies is essential because these studies can influence the quality of medical care received by patients [5]. The methodological quality of an article can represent its overall quality and should therefore be assessed at the design, conduct, and analysis steps [6,7]. In addition, any erroneous data can be identified throughout the assessment process, thereby eliminating the erroneous data from clinical care and saving medical expenses [8].…”
Section: Introductionmentioning
confidence: 99%
“…[4] The publication rate varies from 11% to 78%,[6] typically hovering around 30-50%. [712] However, there is no data regarding the publication rate of research presented in anesthesia in an Indian scenario.…”
Section: Introductionmentioning
confidence: 99%